Antibacterial and Antioxidant Activities of Cocoa Pod that Associated in Maltodextrin in Various Concentration - Asriani Hasanuddin; Hafsah Hafsah; Chairil Anwar; Marhawati Mappatoba (Universitas Tadulako, 2018)
Cocoa pod extract ((Theobroma cacao L.) has antioxidant and antimicrobial activity that has the potential as a natural food preservative. However, in its use the cocoa fruit skin extract has a disadvantage because the short shelf time and its application to food are limited, efforts are needed to prevent damage and extend shelf life, one of the efforts that can be done is by encapsulating the extract.This study aims to determine the antibacterial activity and antioxidant encapsulation of cocoa peel extract, this study begins with the extraction of cocoa pods with ethanol solvent by comparing cocoa pods : solvent 1: 4 The skin of cacao cocoa fruit used is yellow harvested cocoa fruit, then chopped and dried to form flour.The sample is extracted by maceration with ethanol solvent Antioxidant test is done by DPPH method, while antibacterial test is carried out by the well diffusion method. This study used a completely randomized design method (CRD) with 5 treatments using a maltodextrin concentration of 20% (M1); 30% (M2); 40% (M3); 50% (M4) and 60% (M5). The results showed that the treatment gave the highest yield in the treatment of 60% maltodextrin concentration (M5), while the highest antioxidant activity was obtained in the treatment of 20% maltodextrin (M1) with IC50 75.98 µg / mL and the treatment with the lowest antioxidant activity was obtained at treatment of 60% maltodextrin concentration (M5) with IC50 value 114.89 µg / mL. While for the antimicrobial activity also obtained with the same results, namely treatment of 20% (M1) obtained a higher inhibition diameter compared to treatment at 30%; 40%; 50% and 60% for all types of bacteria. The inhibition diameter in the treatment of the concentration of maltodextrin 20% (M1) for E. coli bacteria is between 4.12 mm - 10.95 mm, Salmonella sp is 2.85 mm - 8 , 25 mm and for Staphylococcusaureus of 5.15 mm - 13.90 mm and the lowest inhibition diameter was obtained in the treatment of 60% maltodextrin concentration (M5) for E. coli bacteria of between 2.0 mm - 4.79 mm, Salmonella sp of 1.15 mm - 4.35 mm and for Staphylococcusaureusat 2.76 mm - 5.17 mm.This study concluded that the encapsulation of cocoa peel extract using 20% maltodextrin had the highest antioxidant and antimicrobial activity when compared with other treatments namely 30% concentration; 40%; 50% and 60% but for the treatment of 20% and 30% there is no difference. Ethanol extract of cocoa pods can be made in the form of encapsulates which are very likely to be used as natural preservatives.